2017
DOI: 10.17816/ptors5213-21
|View full text |Cite
|
Sign up to set email alerts
|

TENS for the surgical management of femoral shaft fractures in 6-14 years age group children

Abstract: Актуальность. Перелом диафиза бедра один из наиболее распространенных переломов, встречающихся в дет-ском возрасте. Как правило, дети в возрастной группе 6-14 лет лечатся с помощью скелетного вытяжения, ин-трамедуллярного остеосинтеза либо аппаратами внешней фиксации. Мы провели клинические исследования, в которых использовали только TENS (титановая эластичная стержневая система) при лечении переломом диафиза бедренной кости у детей. Методы. В данное исследование вошли 45 случаев переломов диафиза бедренной ко… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Thirty-nine patients with femur fractures out of 100 patients have taken part in this study, with a mean age of 6.21+/-2.64 years. No complications were observed in 6 patients (15%), comparing this finding to a study by Amin et al where 15 of 18 patients (88.80%) have had no complications 11 . We have found that Insertion site irritation happened in 28 patients (71.79%), where 9 of them were associated with joint swelling (23%), and only one patient had skin breakdown that necessitated operative trimming of the nail ends and clinical follow-up for union progress did not interfere furthermore.…”
Section: Discussionsupporting
confidence: 69%
“…Thirty-nine patients with femur fractures out of 100 patients have taken part in this study, with a mean age of 6.21+/-2.64 years. No complications were observed in 6 patients (15%), comparing this finding to a study by Amin et al where 15 of 18 patients (88.80%) have had no complications 11 . We have found that Insertion site irritation happened in 28 patients (71.79%), where 9 of them were associated with joint swelling (23%), and only one patient had skin breakdown that necessitated operative trimming of the nail ends and clinical follow-up for union progress did not interfere furthermore.…”
Section: Discussionsupporting
confidence: 69%
“…However, Martinez [5] reported excessive shortening and angular deformity in around 43 % of their patients treated by an early spica cast. Hughes [6] studied the impact of immediate spica casting on patients and families following femoral shaft fractures.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the greatest problems encountered by the family in caring for a child in a spica cast were transportation, cast intolerance by the child, and keeping the child clean [4][5][6]. Although most authors still recommend conservative methods of treatment in pediatric femur fractures in preschool children, there is still confusion regarding the optimal method for children beyond this age group [7].…”
Section: Introductionmentioning
confidence: 99%